Słownik języka miyako Nikołaja Newskiego: rekonstrukcja oraz analiza etnolingwistyczna rękopisu - Jarosz, Aleksandra (My University, 2016)
Dysertacja poświęcona jest rekonstrukcji oraz analizie rękopiśmiennych notatek leksykograficznych z lat dwudziestych XX wieku autorstwa rosyjskiego orientalisty Nikołaja Newskiego – niżej: „Materiały”. „Materiały” są nieukończonym, pozostawionym na roboczym etapie szkicem wielojęzycznego (miyako-japońsko-rosyjskiego) słownika języka miyako, poważnie zagrożonego języka z rodziny japonicznej, rodzimego dla wysp Miyako w subarchipelagu Sakishima archipelagu Ryukyu. Źródło to jest kluczowe dla dokumentacji i rewitalizacji języka miyako, a w szerszej perspektywie – dla badań nad całą rodziną japoniczną. Projekt autorki był pierwszym od czasu powstania „Materiałów” systematycznym i skutecznym wysiłkiem dążącym do akademickiej publikacji słownika Newskiego. Jedna część dysertacji, The reconstructed dictionary, stanowi zasadniczo wierne odtworzenie „Materiałów”, przy sporadycznych interwencjach redakcyjnych mających na celu poprawienie czytelności i spójności źródła. Druga część, Studies on the manuscript, składa się z trzech rozdziałów, czterech indeksów oraz pięciu dodatków. Rozdział pierwszy dotyczy tła powstania „Materiałów” oraz ich leksykograficznej zawartości. Rozdział drugi zawiera autorski opis języka miyako z lat dwudziestych oparty na materiale zrekonstruowanym ze słownika Newskiego. Rozdział trzeci ma za zadanie ustalić rangę „Materiałów” na tle riukiuanistycznego dorobku naukowego oraz wartość tkwiącą w ich rekonstrukcji, opracowywaniu i przyszłej publikacji. Dysertacja zawiera także stworzony w oparciu o „Materiały” mini-słownik miyako-angielski.

The present dissertation is devoted to the reconstruction of handwritten lexicographic notes compiled in 1920s by a Russian orientalist Nikolay Nevskiy, henceforth the Materials. The Materials are an unfinished draft of a trilingual dictionary of Miyakoan, a seriously endangered minority language native to the Miyako islands in the Sakishima subarchipelago in the Ryukyus, Japan. This draft is a source of paramount importance to the documentation and revitalization of Miyakoan and, by extension, to the study of Japonic languages in general. This author’s Ph.D. project has been the first systematic and successful attempt at an academic publication of Nevskiy’s dictionary. One part of the dissertation, entitled The reconstructed dictionary, is essentially a faithful reconstruction of the Materials minimally edited for legibility, consistency and an overall user-friendliness. The other part, Studies on the manuscript, consists of three chapters, four indeces and five appendices. Chapter One discusses the background of the Materials and their lexicographic content. Chapter Two involves an original description of Miyakoan from the 1920s based on the data recovered from Nevskiy’s dictionary. Chapter Three aims at establishing the merit of the Materials against the background of other achievements in Ryukyuan linguistics, as well as the value of the reconstruction, editing and future publishing of the source. A Miyakoan-English wordlist based on the Materials has also been appended to the dissertation. In all likelihood, it is the first Miyakoan-English lexicographic source to have ever been published.
Nikolay Nevskiy’s Miyakoan dictionary: reconstruction from the manuscript and its ethnolinguistic analysis
Wydział Neofilologii: Katedra Orientalistyki
Keywords: miyako; języki japoniczne; Newski; leksykografia; dokumentacja językowa; Miyakoan; Japonic; Nevskiy; lexicography; language documentation